Williams gynecology - Hoffman, Barbara L.; Williams, J. Whitridge (John Whitridge) (McGraw-Hill Medical, 2012)
"Unlike all other gynecology books that focus solely on either the medical OR surgical aspects of the discipline, Williams Gynecology provides both in one competitively priced volume. Students, residents, and physicians no longer have to choose which book to purchase or pay double for the content. A team of medical illustrators were contracted to complete hundreds of original illustrations for both the surgical atlas and medical reference portions of Williams Gynecology. The result is an entirely unique and instructionally consistent art program unlike any other"--Provided by publisher.